PVC containing silver nanoparticles with antimicrobial properties effective against SARS-CoV-2 - da Silva, Daniel J.; Gramcianinov, Guilherme B.; Jorge, Pamela Z.; Malaquias, Vanessa B.; Mori, Augusto A.; Hirata, Mário H.; Lopes, Sergio A. M.; Bueno, Luciano A.; Champeau, Mathilde; Carastan, Danilo J. (Frontiers in Chemistry, 2023)
Silver nanoparticles (AgNPs) are effective antimicrobial agents against several pathogens, being widely used in the manufacture of polymeric nanocomposites with self-disinfecting properties, including Poly(vinyl chloride) (PVC) that is a polymer without enough antimicrobial performance to kill pathogens immediately after direct surface contact. Self-disinfecting characteristics are desired in PVC since it is used in goods exposed to contamination by biohazardous in hospitals, medical clinics, ambulatories, and dental clinics. Herein, PVC/AgNP nanocomposites present the capacity to inactivate SARS-CoV-2 particles using a low amount of AgNP (0.3 wt%). Also, several interesting findings about the relationships among the morphology, polymer chemical structure, and properties of the polymeric nanocomposites are reported here.